Impulsivity, Lack of Premeditation, and Debts in Online Gambling Disorder - López-Torres, Isabel; León-Quismondo, Leticia; Ibáñez, Angela (Frontiers in Psychiatry, 2021)
Background and Objectives: Gambling disorder (GD) is a recurrent and persistent problematic gambling behavior that impairs multiple areas of an individual's life. GD can persist through two modes: online or offline. This study aims to compare sociodemographic, clinical, and psychological characteristics between treatment-seeking online and offline gamblers and analyze the effect of the gambling mode (online or offline) on anxiety, depression, impulsivity, and debts. Methods: 79 treatment-seeking gamblers (96.2% males), who were simultaneously receiving treatment at a specialized Pathological Gambling and Behavioral Addictions Unit, participated in this study. The sample was divided into two subsamples: online (n=29, 100% males) and offline (n=50, 94% males); the characteristics of these two groups were compared and analyzed using Chi-Square test (χ2), t-Test or Mann-Whitney U test (p<0.05). Multiple linear regression analyses were performed to determine the effects of gambling mode on significant variables (lack of premeditation and debts). Results: The online sample with a mean age of 29.4 years mainly chose to engage in sports betting (45%, p<0.05) and showed a higher lack of premeditation levels (25.8 points, p<0.05) than the offline sample. In addition, the online sample was younger with respect to their onset to gambling (20.2 years, p<0.05) and the beginning of their gambling problems (25 years, p<0.05) compared to the offline sample. Online gambling increased the levels of lack of premeditation by an average of 5.43 points compared to offline gambling (p<0.05). Accumulated debts of the online sample were lower (€11,000) than those of the offline sample (€12,000). However, the interaction between age and gambling mode revealed that online gamblers increased their debt amounts with age at an average increase of €2,726.33 per year compared to offline gamblers (p<0.05). No significant influence of gambling mode was found on GD severity, anxiety, and depression levels. Conclusions: Gambling mode has a significant relationship with lack of premeditation—a component of impulsivity—and accumulation of debts in treatment-seeking people with GD; however, no relationship was found with the rest of the variables analyzed. Future research with larger samples is needed to confirm these findings.